Strengthening Digital Literacy in Islamic Religious Education: A Systematic Literature Review - Kusbiantoro, Handaru; Syafiq, Ahmad; Firdosi, Akh. Fad; Taufiqurrahman, Taufiqurrahman (FITRAH: International Islamic Education Journal, 2026)
Rapid digital technological development has transformed learning practices, including Islamic Religious Education (IRE), requiring the strengthening of digital literacy integrated with Islamic values. This study aims to synthesize the development of digital literacy research in IRE learning through a Literature Systematic Review (LSR) approach based on PRISMA 2020. Data were obtained from 15 selected articles and analyzed thematically to identify concepts, implementation strategies, benefits, challenges, and research gaps. The findings show that digital literacy in IRE is not only limited to technical skills but also includes critical, ethical, and spiritual dimensions integrated with the values of tabayyun, amanah, and ṣidq. Digital literacy implementation is carried out through Learning Management Systems, interactive learning media, educational videos, and project- and problem-based learning models. The study also reveals improvements in learning motivation, critical thinking skills, religious literacy, and students’ character building. However, challenges remain, including limited teacher competence, infrastructure constraints, and risks of misinformation. This research provides both conceptual and practical contributions for developing Islamic education learning in the modern digital era and serves as a reference for future research development in education.